Characteristics and Clinical Outcomes of COVID-19 Patients with Hyperglycemia: Retrospective Cohort Study from a COVID-19 Referral Hospital, Bandung, Indonesia - Permana, Hikmat; Ikhsanawati, Annisa; Susandi, Evan; Soetedjo, Nanny Natalia Mulyani; Alisjahbana, Bachti (Althea Medical Journal, 2023)
Background: COVID-19 often causes severe complications in patients with metabolic disorders such as diabetes mellitus. Conversely, inflammation caused by infection may also trigger insulin resistance, resulting in hyperglycemia and is related to the disease severity. This study aimed to describe the characteristics and clinical outcomes of COVID-19 patients with hyperglycemia at one of the COVID-19 referral hospitals in Bandung, Indonesia.Methods: This retrospective cohort study used secondary data from medical records of COVID-19 patients admitted to Dr. Hasan Sadikin General Hospital Bandung, Indonesia from March 2020 to March 2021. This study included all patients with confirmed COVID-19, aged >18 years, and had at least one blood glucose test at admission. Patients were grouped based on three possible types of hyperglycemia, namely diabetes mellitus, reactive hyperglycemia, and steroid-induced hyperglycemia; then their characteristics and disease outcomes were compared. Results: This study identified 1,114 patients’ medical records and included 1,013 data in the analysis. Hyperglycemia occurred in 45.1% of COVID-19 patients. The most common hyperglycemia types were diabetes mellitus (55.7%), reactive hyperglycemia (37.4%), and steroid-induced hyperglycemia (7%). The steroid-induced hyperglycemia group had similar characteristics as the diabetes group. The reactive hyperglycemia group exhibited a metabolic syndrome pattern resembling pre-diabetic conditions. The highest rates of severe disease and mortality were seen in the steroid-induced hyperglycemia group, followed by the diabetes group.Conclusions: There is an elevated prevalence of hyperglycemia in COVID-19 patients with diabetes. The steroid-induced hyperglycemia group has the most unfavorable outcomes. These observations emphasize the importance of identifying hyperglycemic conditions to improve management and outcomes.